Connectomics signatures of prenatal cocaine exposure affected adolescent brains. Issue 10 (28th March 2012) - Li, Kaiming; Zhu, Dajiang; Guo, Lei; Li, Zhihao; Lynch, Mary Ellen; Coles, Claire; Hu, Xiaoping; Liu, Tianming
<x xml:space="preserve">Abstract</x> Recent in vivo neuroimaging studies revealed that several brain networks are altered in prenatal cocaine exposure (PCE) affected adolescent brains. However, due to a lack of dense and corresponding cortical landmarks across individuals, the systematical alterations of functional connectivities in large‐scale brain networks and the alteration of structural brain architecture in PCE affected brain are largely unknown. In this article, we adopted a newly developed data‐driven strategy to build a large set of cortical landmarks that are consistent and corresponding across PCE adolescents and their matched controls. Based on these landmarks, we constructed large‐scale functional connectomes and applied the well‐established approaches of deriving genomics signatures in genome‐wide gene expression studies to discover functional connectomics signatures for the characterization of PCE adolescent brains. Results derived from experimental data demonstrated that 10 structurally disrupted landmarks were identified in PCE, and more importantly, the discovered informative functional connectomics signatures among consistent landmarks distinctively differentiate PCE brains from their matched controls. Hum Brain Mapp 34:2494–2510, 2013. © 2012 Wiley Periodicals, Inc.